Experimental investigation of heat-treated aluminum profiles - Merklein, Marion; Graser, Matthias; Lechner, Michael (Key Engineering Materials, 2015)
Tailor Heat Treated Profiles (THTP) are profiles that exhibit local different mechanical properties optimized for a subsequent forming operation. The property distribution is realized by short term heat treatment before a forming operation. Based on the interaction of soft and hard areas the material flow can be improved and the formability can be enhanced. Prerequisite for a successful application of the technology is a comprehensive material characterization. Therefore, within this paper the influence of short term heat treatment on the mechanical properties of profiles will be presented. In particular, different heating technologies based on heat conduction and laser radiation are compared. Based on the results, a process window will be derived. All investigations were performed using the precipitation hardenable aluminum alloy EN AW 6060.
LFT Import::2019-07-29 (2112)
Keywords: Aluminum profiles; Characterization; Tailored heat treatment